The Transcription Factor ZNF683/HOBIT Regulates Human NK-Cell Development - Post, Mirte; Cuapio, Angelica; Osl, Markus; Lehmann, Dorit; Resch, Ulrike; Davies, David M.; Bilban, Martin; Schlechta, Bernhard; Eppel, Wolfgang; Nathwani, Amit; Stoiber, Dagmar; Spanholtz, Jan; et al. (Frontiers in Immunology, 2017)
We identified ZNF683/HOBIT as the most highly upregulated transcription factor gene during ex vivo differentiation of human CD34+ cord blood progenitor cells to CD56+ NK cells. ZNF683/HOBIT mRNA was preferentially expressed in NK cells compared to other human peripheral blood lymphocytes and monocytes. During ex vivo differentiation, ZNF683/HOBIT mRNA started to increase shortly after addition of IL-15 and further accumulated in parallel to the generation of CD56+ NK cells. shRNA-mediated knockdown of ZNF683/HOBIT resulted in a substantial reduction of CD56-CD14- NK-cell progenitors and the following generation of CD56+ NK cells was largely abrogated. The few CD56+ NK cells, that escaped the developmental inhibition in the ZNF683/HOBIT knockdown cultures, displayed normal levels of NKG2A and KIR receptors. Functional analyses of these cells showed no differences in degranulation capacity from control cultures. However, the proportion of IFN-γ producing cells appeared to be increased upon ZNF683/HOBIT knockdown. These results indicate a key role of ZNF683/HOBIT for the differentiation of the human NK-cell lineage and further suggest a potential negative control on IFN-γ production in more mature human NK cells.